2019
DOI: 10.1108/jsm-03-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Brand engagement and experience in online services

Abstract: Purpose The purpose of this study is to assess the mediating role of brand trust and commitment in the relationship of brand engagement and brand experience with brand loyalty in the online service context. Design/methodology/approach To achieve the study’s objective, 414 users of virtual service brands, predominantly in the online banking, airline and hotel sectors, were surveyed. Findings Both brand engagement and experience exert direct effects on brand trust and commitment, as well as indirect effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 97 publications
6
75
0
24
Order By: Relevance
“…For this reason, maintaining harmonious relationships among consumers is a crucial driver of success and the survival of a social media brand page (Luo et al 2016). In addition, consumer-brand relationships that integrate consumer-other consumers relationships contribute to enhance such harmony (Zhang and Luo 2016), and the engagement consumers have with the brand depends on the benefits they perceived from brand actions on social media (see, for instance, Schivinski et al 2019;Khan et al 2019). The former focus on interactions with consumers and the brand or the company behind the brand; a point that has been confirmed in the literature concerning the brand relationship that has shown that consumers tend to invest in a relationship to a brand (Algesheimer et al 2005;Fournier 1998).…”
Section: Community Relationships In Social Media: Brand Versus Consummentioning
confidence: 99%
“…For this reason, maintaining harmonious relationships among consumers is a crucial driver of success and the survival of a social media brand page (Luo et al 2016). In addition, consumer-brand relationships that integrate consumer-other consumers relationships contribute to enhance such harmony (Zhang and Luo 2016), and the engagement consumers have with the brand depends on the benefits they perceived from brand actions on social media (see, for instance, Schivinski et al 2019;Khan et al 2019). The former focus on interactions with consumers and the brand or the company behind the brand; a point that has been confirmed in the literature concerning the brand relationship that has shown that consumers tend to invest in a relationship to a brand (Algesheimer et al 2005;Fournier 1998).…”
Section: Community Relationships In Social Media: Brand Versus Consummentioning
confidence: 99%
“…Van Doorn et al (2010) argue that, for the customers, the engagement enhances their perceptions, attitudes, emotions, and social identities related to the product or brand. For the online service, consumers who have high level brand engagement lead to high level brand trust, brand commitment and brand loyalty (Khan et al, 2019). For an enterprise, it leads to gains economic benefit, reputation, competitive advantage, and product improvements.…”
Section: Consequencesmentioning
confidence: 99%
“…Konsumen pada umumnya memiliki keinginan dalam niat melakukan pembelian yang lebih tinggi dengan merek yang dikenali dengan mudah. Komitmen merek terdiri dari dua dimensi yaitu kesinambungan dan komitmen afektif (Khan et al, 2019). Brand experience didefinisikan sebagai tanggapan dari konsumen yang dapat ditemukan melalui sensasi, perasaan, kognitif, dan respon perilaku yang ditimbulkan oleh rangsangan yang berkaitan dengan merek dari sisi desain dan identitas, komunikasi, pengemasan, dan lingkungan (Khan et al, 2019).…”
unclassified
“…Komitmen merek terdiri dari dua dimensi yaitu kesinambungan dan komitmen afektif (Khan et al, 2019). Brand experience didefinisikan sebagai tanggapan dari konsumen yang dapat ditemukan melalui sensasi, perasaan, kognitif, dan respon perilaku yang ditimbulkan oleh rangsangan yang berkaitan dengan merek dari sisi desain dan identitas, komunikasi, pengemasan, dan lingkungan (Khan et al, 2019). Dalam layanan online seperti adanya e-commerce, kepercayaan yang telah tercapai diidentifikasi sebagai faktor keberhasilan utama mengingat tidak adanya interaksi secara fisik dan fisik pembeli/jarak layanan (Bilgihan, 2016).…”
unclassified
See 1 more Smart Citation